Nihilism of Tomas Sodeika - Šerpytytė, Rita (Religija ir kultūra, 2008)
The article deals with the thinking of the most famous and original Lithuanian philosopher’s – Tomas Sodeika. The question – what does this thinking conclude and which place in the landscape of Lithuanian philosophical thought it take up? – is being analysed. The article demonstrates, that reality “becomes” the main and unique “theme” of Tomas Sodeika textes. By interpreting these textes, the fundamental non-identitness and non-commonality between text (textual level) and reality and it’s nihilistic character as well, as the main insight of Sodeikas’ textes, is being disclosed.
Keywords: Tomas Sodeika; thinking; reality; text; nihilism